Low voltage area as a predictor of recurrence after a single pulmonary vein isolation procedure: results of the WAVE-MAP AF study. (3rd October 2022) - Starek, Z; Di Cori, A; Betts, T; Clerici, G; Gras, D; Lyan, E; Della Bella, P; Li, J; Hack, B; Zitella Verbick, L; Sommer, P
Abstract: Background/Introduction: Pulmonary vein isolation (PVI) is a recommended approach for atrial fibrillation (AF) ablation procedures. Substrate modification beyond PVI has mixed results but identifying and ablating low voltage zones and ablating those targets in addition to PVI may be beneficial. Electroanatomic mapping is critical to identify subjects that may require further substrate modification. Low voltage area may be predictive of optimal treatment approach. Purpose: This was a prospective, multicenter, interventional study of a high-density grid-style mapping catheter (HD Grid) to characterize left atrial low voltage substrate during sinus rhythm (SR) and AF and identify associations with 12 month recurrence rates after a single de novo radiofrequency (RF) ablation using a PVI only approach. Methods: This study (NCT03882021) enrolled 300 subjects at 18 centers in Europe and Israel. Subjects underwent de novo RF ablation for paroxysmal AF (PAF) (N=113), early persistent AF (PsAF; AF sustained 7 days to 3 months) (N=86) or non-early PsAF (AF sustained >3 months to 12 months) (N=101). High density voltage maps were collected with HD Grid. Two pre-ablation maps, in SR and AF, were created for each subject (N=196) followed by PVI only ablation. Low voltage area (using cutoffs of 0.1 mV to 1.5 mV) was investigated in SR and AF. Follow up visits were at 3, 6 and 12 months post-ablation, with a 24-hour Holter monitor at 12 months. A Cox proportional hazards model was used to identify associations between mapping data and 12 month AF/atrial flutter (AFL)/atrial tachycardia (AT) recurrence after a single PVI procedure. Results: At 12 months, 75.5% of subjects were free from AF/AFL/AT recurrence. On average, PsAF subjects had more low voltage area than PAF subjects in SR and AF. However, while univariate analysis found no correlation between recurrence and PAF or PsAF diagnosis (p=0.1261), those with recurrence had a significantly larger percent left atrial low voltage area under 0.5 mV with simultaneous orthogonal bipole wave configuration (HDW) in both AF (p=0.0011) and SR (p=0.0210) than those without recurrence. Using HDW, low voltage area (identified as <0.5 mV) greater than 28% of the left atrium in SR (HR: 4.82, 95% CI: 2.08–11.18, p=0.0003) and greater than 72% in AF (HR: 5.66, 95% CI: 2.34–13.69, p=0.0001) were associated with a higher risk of AF/AFL/AT recurrence at one year. Conclusion(s): Using a standard cutoff of 0.5 mV, a larger percent low voltage area was associated with increased risk of recurrence in both SR and AF. Future analyses will explore optimal low voltage cutoffs and thresholds predictive of recurrence that may necessitate additional substrate modification beyond PVI. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott